Identification of High Yielding Tropical Strawberry Genotypes by Assessment of Yield Attributing Traits under Field Condition - Akter, Mahmuda; Hossain, Mofazzal; Haque, Azizul; Ivy, Nasrin Akter (Agricultural Development, 2017)
In this study, eight different genotypes namely FA-006, FA-007, FA-008, FA-015, FA-016, FA-017, FA-022 and BARI Strawberry-1 were grown under field condition to evaluate the superior performance of tropical strawberry genotypes in terms of their morphological characters. Our results revealed that FA-015 genotype showed better performance in terms of plant height, leaf number, canopy spread, flowers plant-1, fruit set compared to other genotypes. The maximum days (62.29) required for flower initiation was found in the genotype FA-007 while the minimum days (30.59) required for flower initiation was recorded in the genotype FA-016. As regards to the fruit characters (length, width and weight), FA-022 genotype exhibited highest performances compared to other genotypes. Our results also implied that the highest fruit yield plant-1 (213.8g) was obtained from the genotype FA-022 and the highest amount of TSS (10.71%) was found in the genotype BARI Strawberry-1. Genotype FA-015 was superior in respect of growth related parameters and genotype FA-022 found potential in terms of fruit yield. Further research is needed on molecular characterization and marker aided selection of strawberry genotypes.